3-(4-Fluorophenyl)-1-(1-(4-fluorophenyl)-3,3,3-trifluoroprop-1-en-1-yl)-5-fluoro-1H-pyrazole - Paveliev, Stanislav; Ustyuzhanin, Alexander; Krylov, Igor; Terent’ev, Alexander (MolBank, 2023)
In this work, the title compound was synthesized via the visible-light-induced radical denitrogenative trifluoromethylation of the corresponding vinyl azide followed by Cs2CO3-mediated defluorinative cyclization of the resultant azine. The widely available sodium trifluoromethanesulfinate is used as a precursor of CF3 radicals, while graphitic carbon nitride (g-C3N4) is employed as an environmentally friendly, cheap, and efficient heterogeneous photocatalyst. The structure of the synthesized compound was established by 1H, 13C, 19F-NMR, IR spectroscopy, and mass-spectrometry.